Problematika Pendidikan Terhadap Sistem Pendidikan Modern Melalui Penerapan Kurikulum Merdeka - Fataya, Denanta Qonita (Maliki Interdisciplinary Journal, 2024)
This article was prepared to explain the education system and problems in Indonesia. The implementation of the new curriculum in Indonesia is carried out to catch up after Covid-19. Even though it is considered very effective in meeting quality educational competency standards through teaching methods and media, there are still educational problems that must be immediately addressed by the government and local residents to realize educational goals as stated in the preamble to the 1945 Constitution. The article is prepared using a qualitative descriptive method to describe factual data. The educational problems that occur are caused by several factors, for example the high spike in population growth which has created educational institutions that are not evenly distributed throughout Indonesia.